Pharmaceutical and pharmacokinetic evaluation of a newly formulated multiparticulate matrix of levodopa and carbidopa - Emelia Priscilla Imbeah; Ofosua Adi-Dako; Benoit N'guessan; Kennedy Kwami Edem Kukuia; Benedicta Obenewaa Dankyi; Ismaila Adams; Ebenezer Ofori-Attah; Regina Appiah-Opong; Seth Kwabena Amponsah (International Association of Physical Chemists (IAPC), 2022)
Levodopa is routinely co-administered with carbidopa in the management of Parkinson's disease. Although the aforementioned combination therapy is effective, there may be fluctuating plasma levels of levodopa after oral administration. We formulated and evaluated the kinetic characteristics of the chitosan-pectin-based multiparticulate matrix of levodopa and carbidopa. Pectin was extracted from the cocoa husk, and the chitosan-pectin-based matrix was prepared by wet granulation. Formulations were evaluated for drug-excipient compatibility, drug content, precompression properties and in vitro release. For pharmacokinetic evaluation, rats were put into groups and administered either chitosan-pectin based matrix of levodopa/carbidopa, Sinemet® CR or levodopa/carbidopa immediate release powder. Rats were administered the different formulations of levodopa/carbidopa (20/5 mg/kg) per os every 12 hours. The pharmacokinetic parameters of levodopa were estimated for the various treatment groups. The percentage content of levodopa and carbidopa in the various formulations was within the acceptance criteria. The AUC0-24 for levodopa/carbidopa multiparticulate matrix (Formulation 3: 484.98 ± 18.70 µg.hr/mL); Formulation 4: 535.60 ± 33.04 µg.hr/mL), and Cmax (Formulation 3: 36.28 ± 1.52 μg/mL; Formulation 4: 34.80 ± 2.19 μg/mL) were higher than Sinemet® CR (AUC0-24 262.84 ± 16.73 µg.hr/mL and Cmax 30.62 ± 3.37 μg/mL). The t1/2 of the new formulation was longer compared to Sinemet® CR.